Research for Health Justice: an ethical framework linking global health research to health equity - Bridget Pratt (BMJ Global Health)
Global health research should generate new knowledge to improve the health and well-being of those considered disadvantaged and marginalised. This goal motivates much of the global health research being undertaken today. Yet simply funding and conducting global health research will not necessarily generate the knowledge needed to help reduce health disparities between and within countries. Global health research grants programmes and projects must be structured in a particular way to generate that type of information. But how exactly should they be designed to do so? Through a programme of ethics research starting in 2009, an ethical framework called Research for Health Justice was developed that provides guidance to global health researchers and funders on how to design research projects and grants programmes to promote global health equity. It provides guidance on, for example, what research populations and questions ought to be selected, what research capacity strengthening ought to be performed and what post-study benefits ought to be provided. This paper describes how the ‘research for health justice’ framework was generated and pulls together a body of work spanning the last decade to provide a comprehensive and up-to-date version of its guidance.